2001
DOI: 10.1006/enfo.2001.0070
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Contamination of Fractured Formations by Non-Newtonian Oil Pollutants

Abstract: In many practical applications, non-aqueous phase liquid (NAPL) pollutants exhibiting a clearly non-Newtonian rheological behavior (e.g. crude oil, suspensions of engine oils, asphalt, creosote, etc.) may migrate through fractured formations and contaminate aquifers. The present work is the ®rst step toward the development of non-Darcian models concerning the non-linear NAPL¯ow in single fractures, and determination of the coupled eects of non-Newtonian NAPL rheology and¯ow rate on the transient immiscible dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
(53 reference statements)
1
9
0
Order By: Relevance
“…Our finding supports several recent simulation studies such as Schedl (1992), Mourzenko et al (1995), Brown et al (1995), Choi et al (1997), Oron andBerkowitz (1998), Baker (2000), Kolditz (2001), andBerkowitz (2002), and experimental studies such as Lloyd et al (1996) and Theodoropoulou et al (2001) which indicated that the LCL assumption might be inaccurate in many cases of fracture flow, but disagrees with those that employed the laminar flow and LCL assumptions such as Louis (1969), and Witherspoon et al (1980).…”
Section: Comparison Of the Theoretical And Experimental Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Our finding supports several recent simulation studies such as Schedl (1992), Mourzenko et al (1995), Brown et al (1995), Choi et al (1997), Oron andBerkowitz (1998), Baker (2000), Kolditz (2001), andBerkowitz (2002), and experimental studies such as Lloyd et al (1996) and Theodoropoulou et al (2001) which indicated that the LCL assumption might be inaccurate in many cases of fracture flow, but disagrees with those that employed the laminar flow and LCL assumptions such as Louis (1969), and Witherspoon et al (1980).…”
Section: Comparison Of the Theoretical And Experimental Resultssupporting
confidence: 88%
“…Kohl et al (1997) has reported non-Darcian flow in natural rocks in two independent multirate flow experiments in the hot dry rock (HDR) test site at Soultz of France. Non-Darcian flow behavior was observed for realistic fractures with rough surfaces by many other studies such as Schedl (1992), Lloyd et al (1996), Choi et al (1997), Oron andBerkowitz (1998), Baker (2000), Kolditz (2001), Theodoropoulou et al (2001), andBerkowitz (2002).…”
Section: Introductionmentioning
confidence: 89%
“…The shear viscosity of NWP was measured as a function of the shear stress with a Dynamic Stress Rheometer (SR-200, Rheometrics Inc.) and was fitted to the mixed Meter-andpower-law fluid model [6,22] (Table 1, Fig. 1) given by…”
Section: Methodsmentioning
confidence: 99%
“…In addition, drainage [22] and imbibition [36] experiments with a shear-thinning non-wetting fluid have revealed that the pore-scale mechanisms and transient flow pattern are affected significantly by the non-Newtonian rheology, as well. The question is whether and how the capillary pressure and relative permeability curves, estimated from unsteady-state experiments are correlated with the fluid rheology, or equivalently, with the rate-dependent shear viscosities of non-Newtonian fluids.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation